2017
DOI: 10.11604/pamj.2017.28.216.11441
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients�satisfaction after laparoscopic surgery in a tertiary hospital in Cameroon (Africa)

Abstract: IntroductionAccess to laparoscopy is low in Cameroon where customers' satisfaction has not been reported so far. We assessed patients' satisfaction with the process of care during laparoscopic surgery in a new tertiary hospital.MethodsA questionnaire was addressed to consenting patients (guardians for patients under 18) with complete medical records who underwent laparoscopy at the Douala Gynaeco-Obstetric and Paediatric Hospital (Cameroon) from November 1, 2015 to July 31, 2016. The following modified Likert'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…We report that patients who were dissatisfied commonly complained of long waiting times (13/17, 76%). Other studies from Canada, India, and Cameroon reported similar findings (79%, 73.3%, and 73%, respectively) [ 77 - 79 ].…”
Section: Discussionsupporting
confidence: 66%
“…We report that patients who were dissatisfied commonly complained of long waiting times (13/17, 76%). Other studies from Canada, India, and Cameroon reported similar findings (79%, 73.3%, and 73%, respectively) [ 77 - 79 ].…”
Section: Discussionsupporting
confidence: 66%
“…Tchartchian et al[17] both reported satisfaction levels greater than 90%. Further studies by Buda et al and Fouogue et al[19] [25] also confirm that irrespective of surgical indication, minimally invasive surgery was generally associated with high post-operative patient satisfaction. However, their studies all involved pa-…”
mentioning
confidence: 70%
“…In Cameroon, Fouogue et al in 2017 described high levels of post-operative satisfaction in patients who underwent laparoscopic fertility-enhancing pelvic surgery [19]. Yet studies evaluating patient satisfaction following elective major gynaecological surgery or following major surgery, in general, remain rare in our setting.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study of patients’ satisfaction rating of laparoscopic procedures done in Cameroon has reported that patients were globally satisfied with the process of care but financial and geographical barriers should be addressed [ 30 ].…”
Section: Discussionmentioning
confidence: 99%